Răspuns :
a) 2x - x = 1/ 2 - 1/3
x = 3 - 2 / 6 , numitorul este 6
x = 1 /6
b) 2( 3x - 12 - 4x - 4) = 8x - 27 - 15x
2( - x - 16) = - 7x - 27
- 2x - 32 = - 7x - 27
- 2x + 7x = 32 - 27
5x = 5
x = 5/5
x = 1
c) 2x - x - 5x + 2x = 8/6 - 7/2 + 1/3 + 5/2
x - 3x = 8/6 + 1/3 - 2/2
- 2x = 4/3 + 1/3 - 1, numitorul comun= 3
- 2x = 5/3 - 1
- 2x = 5/3 - 3/3
- 2x = 2/3
x = - 2/3 : 2
x = - 2/3 · 1/2
x = - 2/6
x = - 1/3
d) 2x - 7/6 - 3x + 3 = 2x + 1/15+ 1 - x/15
- x - 7/6 + 3 = 2x - x/15 + 1/15 + 1
- x - 2x + x/ 15 = 1/ 15 + 1 + 7/6 - 3
- 3x + x/ 15 = 1/15 + 7/6 - 2, numitorul comun = 30
- 90x + 4x = 4 + 35 - 60
- 86 x = 39 - 60
- 86x = - 21
x = 21/86
x = 3 - 2 / 6 , numitorul este 6
x = 1 /6
b) 2( 3x - 12 - 4x - 4) = 8x - 27 - 15x
2( - x - 16) = - 7x - 27
- 2x - 32 = - 7x - 27
- 2x + 7x = 32 - 27
5x = 5
x = 5/5
x = 1
c) 2x - x - 5x + 2x = 8/6 - 7/2 + 1/3 + 5/2
x - 3x = 8/6 + 1/3 - 2/2
- 2x = 4/3 + 1/3 - 1, numitorul comun= 3
- 2x = 5/3 - 1
- 2x = 5/3 - 3/3
- 2x = 2/3
x = - 2/3 : 2
x = - 2/3 · 1/2
x = - 2/6
x = - 1/3
d) 2x - 7/6 - 3x + 3 = 2x + 1/15+ 1 - x/15
- x - 7/6 + 3 = 2x - x/15 + 1/15 + 1
- x - 2x + x/ 15 = 1/ 15 + 1 + 7/6 - 3
- 3x + x/ 15 = 1/15 + 7/6 - 2, numitorul comun = 30
- 90x + 4x = 4 + 35 - 60
- 86 x = 39 - 60
- 86x = - 21
x = 21/86